Faktor–Faktor yang Mempengaruhi Kesediaan Berbelanja di Pasar Tradisional Wilayah Kabupaten Sukoharjo - Bambang Nurcahya Ningrum; Purwanto Purwanto (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2018)
Many traditional markets in the Sukoharjo regency are not used by tenants to sell, because the visitors who want to shop are quiet. This study is to see whether risk factors, social beliefs, perceived benefits, perceived ease of use, perception of reputation, and trust, influence the willingness to shop in traditional markets. Population and research sample are people in Sukoharjo Regency. Data analysis in the study was carried out using AMOS (Analysis of Moment Structures). Research respondents were 150 respondents. This research involves students in data collection and in other implementation processes. Based on the results of the study showed that the benefits, perceived ease of use, perception of perception, risk perception, perception of social trust, perception of reputation, did not have a positive effect on the willingness to shop in traditional markets. Consumer attitudes positively influence the willingness to shop in traditional markets. Perceptions of benefits have a positive effect on perceptions of social trust. Perceptions of social trust have a positive effect on perceptions of reputation. Perception of benefits does not have a positive effect on perceptions of reputation. Perception of reputation does not have a positive effect on perceptions of trust. Perceptions of social trust do not have a positive effect on perceptions of trust. Perceptions of trust have a positive effect on consumer attitudes in traditional markets.